Stenose caustique del l’oseophage - Pomi, Jorge; Danza, Rómulo; Pérez Billi, Luis; Beguiristain, Alberto; Nuchowich, Gustavo (Cirugía del Uruguay, 1983)
A case of caustic esophagitis is presented. A poor known surgical procedure esophagectomy by a double approach, cervical and abdominal, as performed. The authors consider this, an elective procedure for benign pathology. It can also be indicated in selected cases of esophagic cancer.